Low-protein diet in puberty impairs testosterone output and energy metabolism in male rats. Issue 3 (June 2018) - de Oliveira, Júlio Cezar; de Moura, Egberto Gaspar; Miranda, Rosiane Aparecida; de Moraes, Ana Maria Praxedes; Barella, Luiz Felipe; da Conceição, Ellen Paula Santos; Gomes, Rodrigo Mello; Ribeiro, Tatiane Aparecida; Malta, Ananda; Martins, Isabela Peixoto; Franco, Claudinéia Conationi da Silva; Lisboa, Patrícia Cristina; et al.
Abstract : We examined the long-term effects of protein restriction during puberty on the function of hypothalamic–pituitary–adrenal (HPA) and hypothalamic–pituitary–gonadal (HPG) axes in male rats. Male Wistar rats from the age of 30 to 60 days were fed a low-protein diet (4%, LP). A normal-protein diet (20.5%) was reintroduced to rats from the age of 60 to 120 days. Control rats were fed a normal-protein diet throughout life (NP). Rats of 60 or 120 days old were killed. Food consumption, body weight, visceral fat deposits, lipid profile, glycemia, insulinemia, corticosteronemia, adrenocorticotropic hormone (ACTH), testosteronemia and leptinemia were evaluated. Glucose-insulin homeostasis, pancreatic-islet insulinotropic response, testosterone production and hypothalamic protein expression of the androgen receptor (AR), glucocorticoid receptor (GR) and leptin signaling pathway were also determined. LP rats were hypophagic, leaner, hypoglycemic, hypoinsulinemic and hypoleptinemic at the age of 60 days ( P  < 0.05). These rats exhibited hyperactivity of the HPA axis, hypoactivity of the HPG axis and a weak insulinotropic response ( P  < 0.01). LP rats at the age of 120 days were hyperphagic and exhibited higher visceral fat accumulation, hyperleptinemia and dyslipidemia; lower blood ACTH, testosterone and testosterone release; and reduced hypothalamic expression of AR, GR and SOCS3, with a higher pSTAT3/STAT3 ratio ( P  < 0.05). Glucose-insulin homeostasis was disrupted and associated with hyperglycemia, hyperinsulinemia and increased insulinotropic response of the pancreatic islets. The cholinergic and glucose pancreatic-islet responses were small in 60-day-old LP rats but increased in 120-day-old LP rats. The hyperactivity of the HPA axis and the suppression of the HPG axis caused by protein restriction at puberty contributed to energy and metabolic disorders as long-term consequences.